Combining early lower eyelid surgery with neuromuscular retraining for synkinesis prevention after facial palsy: the role of the eye in aberrant facial nerve regeneration - Di Stadio, Arianna; Ralli, Massimo; De Luca, Pietro; Sossamon, Jake; Frohman, Teresa C.; Altieri, Marta; La Mantia, Ignazio; Ferlito, Salvatore; Frohman, Elliot M.; Brenner, Michael J. (Frontiers in Neurology, 2024)
Background Facial synkinesis (FS) is a distressing sequela of facial palsy (FP) characterized by involuntary, simultaneous movements of facial muscles occurring during voluntary facial expressions. Treatment of synkinesis is challenging, and preventive methods are needed. Aim This study evaluated the efficacy of physical facial nerve rehabilitation (PFNR) therapy alone vs. PNFR with eyelid surgery to correct lagophthalmos and prevent the onset of synkinesis. Methods Twenty five outpatients were randomized to receive either PFNR alone (neuromuscular retraining and Kabat proprioceptive neuromuscular facilitation) or PNFR and early (90 days after FP onset) eyelid surgery (involving a conservative oculoplastic correction for lagophthalmos with epiphora or ectropion). Comprehensive otolaryngological assessments and Magnetic Resonance Imaging (MRI) were conducted. Synkinesis progression was measured using Another Disease Scale (ADS) at baseline, 3-, 6-, 12-, and 24-months post-treatment. The data were analyzed with ANOVA, τ-test, Chi-Square analyses. Results Patients undergoing eyelid surgery with PFNR showed faster (p < 0.001) and better recovery of facial movements (p < 0.05) than patients receiving PFNR alone comparing T0 and T12 (p < 0.0001). No synkinesis were observed in the PFNR plus surgery group while 37% of patients in PFNR alone had synkinesis (p = 0.03). At 24 months, none of the patients in the surgery group presented synkinesis. Conclusion Combining early surgical treatment of paralytic lagophthalmos or epiphora with PFNR accelerated functional recovery and reduced synkinesis in patients with FP compared to facial rehabilitation alone. Further investigations in larger populations with long-term follow-up are needed. Clinical trial registration https://clinicaltrials.gov/study/NCT06538103, NCT06538103.